Parental perceptions of informed consent in a study of tracheal intubations in neonatal intensive care - Tippmann, Susanne; Schäfer, Janine; Arnold, Christine; Winter, Julia; Paul, Norbert W.; Mildenberger, Eva; Kidszun, André (Frontiers in Pediatrics, 2024)
Obtaining informed consent in neonatal emergency research is challenging. The aim of this study was to assess parental perceptions of informed consent following participation in a clinical trial in neonatal emergency care.This was a supplementary analysis of a randomised controlled trial comparing video and direct laryngoscopy for neonatal endotracheal intubation in the delivery room and neonatal intensive care unit. After obtaining informed consent for the clinical trial, parents were asked to answer a series of self-administered questions about their perceptions of clinical trial participation and the consent process. Informed consent had been given either before birth, after birth but before inclusion in the trial, or after inclusion in the trial.We received responses from 33 mothers and 27 fathers (n = 60) of the 63 preterm and term infants who participated in the study. Fifty-three (89.8%, n = 59) parents agreed that infants should participate in clinical trials, and 51 (85%, n = 60) parents agreed that parents should be asked for informed consent. Fifty-three (89.8%, n = 59) parents felt that their infant's participation in this particular trial would be beneficial. Fifty-two (86.7%, n = 60) parents felt that the informed consent process was satisfactory. One parent (100%, n=1) approached before birth, 23 parents (82.1%, n=28) approached after birth but before enrolment and 26 (83.9%, n=31) parents approached after enrolment were satisfied with the timing of the consent process. Eight (13.3%, n = 60) parents felt